Does feeding induce maximal stimulation of protein balance?. Issue 2 (March 2016) - Liebau, Felix; Norberg, Åke; Rooyackers, Olav
Abstract : Purpose of review: Muscle wasting is dramatic in critically ill patients and related to worsened outcome. The question is whether this can be prevented or reduced by adequate protein feeding. Recommendations for protein requirements are different between different societies, because of limited and weak evidence. Most studies, on which these recommendations are based, use nitrogen balance as primary outcome. However, nitrogen balance to estimate protein needs over short periods, is not reliable. Recent findings: Studies using tracer methodology to assess the effects of feeding on whole-body protein synthesis, breakdown and balance, show that both adult and pediatric critically ill patients can utilize parenterally and enterally given proteins or amino acids to build body protein, and that the extra amino acids are not oxidized. Summary: Recent studies show a positive correlation between protein intake and protein balance, with many patients reaching a positive protein balance. However, many questions remain. Especially whether adult patients should have a constant positive protein balance, whether the route of administration affects utilization, which proteins are synthesized and whether these are beneficial, is more protein better and what is the upper limit, and whether a positive protein balance affects clinical outcome?